Plasmid-Borne and Chromosomal ESBL/AmpC Genes in Escherichia coli and Klebsiella pneumoniae in Global Food Products - Kurittu, Paula; Khakipoor, Banafsheh; Aarnio, Maria; Nykäsenoja, Suvi; Brouwer, Michael; Myllyniemi, Anna-Liisa; Vatunen, Elina; Heikinheimo, Annamari (Frontiers in Microbiology, 2021)
Plasmid-mediated extended-spectrum beta-lactamase (ESBL), AmpC, and carbapenemase producing Enterobacteriaceae, in particular Escherichia coli and Klebsiella pneumoniae, with potential zoonotic transmission routes, are one of the greatest threats to global health. The aim of this study was to investigate global food products as potential vehicles for ESBL/AmpC-producing bacteria and identify plasmids harboring resistance genes. We sampled 200 food products purchased from Finland capital region during fall 2018. Products originated from 35 countries from six continents and represented four food categories: vegetables (n = 60), fruits and berries (n = 50), meat (n = 60), and seafood (n = 30). Additionally, subsamples (n = 40) were taken from broiler meat. Samples were screened for ESBL/AmpC-producing Enterobacteriaceae and whole genome sequenced to identify resistance and virulence genes and sequence types (STs). To accurately identify plasmids harboring resistance and virulence genes, a hybrid sequence analysis combining long- and short-read sequencing was employed. Sequences were compared to previously published plasmids to identify potential epidemic plasmid types. Altogether, 14 out of 200 samples were positive for ESBL/AmpC-producing E. coli and/or K. pneumoniae. Positive samples were recovered from meat (18%; 11/60) and vegetables (5%; 3/60) but were not found from seafood or fruit. ESBL/AmpC-producing E. coli and/or K. pneumoniae was found in 90% (36/40) of broiler meat subsamples. Whole genome sequencing of selected isolates (n = 21) revealed a wide collection of STs, plasmid replicons, and genes conferring multidrug resistance. blaCTX–M–15-producing K. pneumoniae ST307 was identified in vegetable (n = 1) and meat (n = 1) samples. Successful IncFII plasmid type was recovered from vegetable and both IncFII and IncI1-Iγ types from meat samples. Hybrid sequence analysis also revealed chromosomally located beta-lactamase genes in two of the isolates and indicated similarity of food-derived plasmids to other livestock-associated sources and also to plasmids obtained from human clinical samples from various countries, such as IncI type plasmid harboring blaTEM–52C from a human urine sample obtained in the Netherlands which was highly similar to a plasmid obtained from broiler meat in this study. Results indicate certain foods contain bacteria with multidrug resistance and pose a possible risk to public health, emphasizing the importance of surveillance and the need for further studies on epidemiology of epidemic plasmids.